Dynamic and polarized muscle cell behaviors accompany tail morphogenesis in the ascidian Ciona intestinalis. - Yale J Passamaneck; Anna-Katerina Hadjantonakis; Anna Di Gregorio (PLoS ONE)
Background Axial elongation is a key morphogenetic process that serves to shape developing organisms. Tail extension in the ascidian larva represents a striking example of this process, wherein paraxially positioned muscle cells undergo elongation and differentiation independent of the segmentation process that characterizes the formation of paraxial mesoderm in vertebrates. Investigating the cell behaviors underlying the morphogenesis of muscle in ascidians may therefore reveal the evolutionarily conserved mechanisms operating during this process. Methodology/principle findings A live cell imaging approach utilizing subcellularly-localized fluorescent proteins was employed to investigate muscle cell behaviors during tail extension in the ascidian Ciona intestinalis. Changes in the position and morphology of individual muscle cells were analyzed in vivo in wild type embryos undergoing tail extension and in embryos in which muscle development was perturbed. Muscle cells were observed to undergo elongation in the absence of positional reorganization. Furthermore, high-speed high-resolution live imaging revealed that the onset and progression of tail extension were characterized by the presence of dynamic and polarized actin-based protrusive activity at the plasma membrane of individual muscle cells. Conclusions/significance Our results demonstrate that in the Ciona muscle, tissue elongation resulted from gradual and coordinated changes in cell geometry and not from changes in cell topology. Proper formation of muscle cells was found to be necessary not only for muscle tissue elongation, but also more generally for completion of tail extension. Based upon the characterized dynamic changes in cell morphology and plasma membrane protrusive activity, a three-phase model is proposed to describe the cell behavior operating during muscle morphogenesis in the ascidian embryo.